Association between two painful and poorly understood conditions: Irritable bowel and sensitive skin syndromes. (4th September 2018) - Misery, Laurent; Duboc, Henri; Coffin, Benoit; Brenaut, Emilie; Huet, Flavien; Taieb, Charles
Abstract: Background: Irritable bowel and sensitive skin syndromes are common painful conditions that are poorly understood, with alterations of the peripheral (and possibly central) nervous system that lead to a lowering of perception thresholds as the main pathophysiological mechanism. Methods: A cross‐sectional epidemiological study was carried out on a representative sample of French people, according to the quota method using a questionnaire. Results: Among the 5, 000 respondents, 48.9% were men and 51.1% were women. According to the adapted Rome questionnaire, 14.6% suffered from irritable bowel syndrome. A total of 59.1% declared very sensitive or sensitive skin. A total of 73.1% of subjects had irritable bowel syndrome versus 52.3% in the other group without an irritable colon ( p  < 0.001). Similarly, the frequency of irritable bowel syndrome symptoms was associated with the severity of sensitive skin syndrome. The presence of sensitive skin was highly associated with the presence of abdominal pain or discomfort, with an OR of 1.93 after adjustment for sex and age. Conclusions: This study is the first study showing an association between sensitive skin and irritable bowel syndromes. Sensory symptoms are predominant in these two syndromes and transit disorders in one case and vasomotor disorders in the other could probably be considered as pathophysiological equivalents. Significance: The demonstration of the association between these two syndromes can open new pathophysiological or even therapeutic pathways, since dysfunctional nerve endings and/or increased release of some neurotransmitters are likely involved.